Time complexity of finding Compatible Wellness Groups in the Wellness Profile Model - Juneam N. (IEEE Computer Society, 2014)
This article describes the Wellness Profile Model. The two decision problems related to the model called the Compatible Wellness Group with Target Member Problem and the Compatible Wellness Group Problem are defined. We propose the two polynomial-time algorithms for solving the two problems here. Our main contribution is to show that the time complexities of these two problems are in class P. © 2014 IEEE.